Executive Committee Minutes 2019-01-24 - Academic Senate:::::::::
Agenda – Approved. Minutes of 12/6/18 – Approved. Chair Report. President Report. Follow up on Faculty Retreat. Statewide Senator Report. Reassigned time for '19 –'20. President's Climate Change Commitment – approved to present to Senate. Faculty Eligible for Emeritus Status – approved for Senate consent calendar. Discontinuance: Edu TESOL concentration – approved as business for the Senate agenda. Vice Chair Report. Vice President of Administration and Finance Report. EPC Report. Associated Student Report. APARC Report. Senate Agenda approved. FSAC Report. SAC Report. SEC Ex Com Rep report.